Pain Assessment--Can it be Done with a Computerised System? A Systematic Review and Meta-Analysis - Pombo, Nuno; Garcia, Nuno; Bousson, Kouamana; Spinsante, Susanna; Chorbev, Ivan (MDPI AG, 2016)
Mobile and web technologies are becoming increasingly used to support the treatment of chronic pain conditions. However, the subjectivity of pain perception makes its management and evaluation very difficult. Pain treatment requires a multi-dimensional approach (e.g., sensory, affective, cognitive) whence the evidence of technology effects across dimensions is lacking. This study aims to describe computerised monitoring systems and to suggest a methodology, based on statistical analysis, to evaluate their effects on pain assessment.